2011
DOI: 10.1111/j.1439-0272.2011.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor sperm quality and advancing age are associated with increased sperm DNA damage in infertile men

Abstract: With increasing evidence for faulty paternal contribution to reproduction, there has been a steady increase in studies highlighting an association between sperm DNA damage, failed/delayed fertilisation and aberrant embryo development. Owing to prevailing ambiguity, the aims of the study were to analyse the genetic integrity of the male gamete and then to understand its association with age, standard semen parameters, lifestyle and occupational factors. The study included 504 subjects, attending university infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(52 citation statements)
references
References 65 publications
10
40
0
Order By: Relevance
“…To date, the published data on the relationship between sperm DNA integrity and normal morphology are conflicting. Although some studies have shown that abnormal sperm morphology and DNA damage are related [20,61] other studies have not identified a significant relationship between these parameters [34,62]. Our data are convincing in view of the fact that the study involves a large cohort of infertile couples with very well defined sperm defects.…”
Section: Discussionsupporting
confidence: 58%
“…To date, the published data on the relationship between sperm DNA integrity and normal morphology are conflicting. Although some studies have shown that abnormal sperm morphology and DNA damage are related [20,61] other studies have not identified a significant relationship between these parameters [34,62]. Our data are convincing in view of the fact that the study involves a large cohort of infertile couples with very well defined sperm defects.…”
Section: Discussionsupporting
confidence: 58%
“…One paradigm that perfectly illustrates the power of these associations is paternal ageing. Thus, numerous studies demonstrate that paternal age is associated with a high incidence of DNA damage in human spermatozoa (Schmid et al, 2007;Singh et al, 2003;Varshini et al, 2012) as well as an increase in the mutational load subsequently carried by the offspring (Kong et al, 2012). Whether there is a mechanistic link between DNA damage in the germ line on the one hand and increased mutation rates in the embryo on the other is a critical issue that remains unresolved.…”
Section: Implications For Future Generations' Healthmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that time to achieve pregnancy is also highly affected by male aging [25]. These evidences raise serious concerns regarding the adverse impacts of APA on the offspring, as it has been confirmed that sperm DNA damage is closely associated with APA [26,27]. Although a decrease in male fertility occurs with age, there is still the need to define an age threshold for which the risk of an adverse outcome due to APA is greater than the gain.…”
Section: Introductionmentioning
confidence: 99%